Credit risk rating systems at large US banks - Treacy, William F; Carey, Mark (Journal of Banking & Finance, 2000)
Internal credit risk rating systems are becoming an increasingly important element of large commercial banks’ measurement and management of the credit risk of both individual exposures and portfolios. This article describes the internal rating systems presently in use at the 50 largest US banking organizations. We use the diversity of current practice to illuminate the relationships between uses of ratings, different options for rating system design, and the effectiveness of internal rating systems. Growing stresses on rating systems make an understanding of such relationships important for both banks and regulators.